Effects of Liquid-to-Solid Ratio and Reaction Temperature on NaOH Pretreatment of Achnatherum splendens - Tao, L.; Ren, J.; Yu, F.K.; Ni, T.R. (Asian Journal of Chemistry, 2013)
In this study, the effects of several factors on NaOH pretreatment of Achnatherum splendens were investigated. It was found that NaOH loading, liquid-to-solid ratio and reaction temperature all had significant effects on delignification. These factors also had significant effects on the contents of lignin, hemicellulose and cellulose in the solids after NaOH pretreatment. The optimal pretreatment conditions were found to be 15 % of NaOH loading, 10:1 of liquid-to-solid ratio, 90 ºC and 90 min of reaction time. Under the optimal conditions, approximate 39 % of lignin was solubilized and the cellulose content was increased to 68.39 % while the lignin and hemicellulose contents were decreased to 9.28 %, 19.86 %, respectively. The lignin was effectively removed by NaOH pretreatment under mild conditions. The results could be considered as a step towards the optimization of NaOH pretreatment of Achnatherum splendens.